Donor organ intervention before kidney transplantation: Head-to-head comparison of therapeutic hypothermia, machine perfusion, and donor dopamine pretreatment. What is the evidence? - Schnülle, Peter; Drüschler, Katharina; Schmitt, Wilhelm; Benck, Urs Tobias; Zeier, Martin; Krämer, Bernhard; Opelz, Gerhard (American journal of transplantation, 2019)
Therapeutic hypothermia, hypothermic pulsatile machine perfusion (MP), and renal-dose dopamine administered to stable brain-dead donors have shown efficacy to reduce the dialysis requirement after kidney transplantation. In a head-to-head comparison of the three major randomized controlled trials in this field, we estimated the number-needed-to-treat for each method, evaluated costs and inquired into special features regarding long-term outcomes. The MP and hypothermia trials used any dialysis requirement during the first postoperative week, whereas the dopamine trial assessed >1 dialysis session as primary endpoint. Compared to controls, the respective rates declined by 5.7% with MP, 10.9% with hypothermia, and 10.7% with dopamine. Costs to prevent one endpoint in one recipient amount to approximately $17 000 with MP but are negligible with the donor interventions. MP resulted in a borderline significant difference of 4% in 3-year graft survival, but a point of interest is that the preservation method was switched in 25 donors (4.6%) for technical reasons. Graft survival was not improved with dopamine on intention-to-treat but suggested an exposure-response relationship with infusion time. MP was less efficacious and cost-effective to prevent posttransplant dialysis. Whether the benefit on early graft dysfunction achieved with any method will improve long-term graft survival remains to be established.
First published: 31 July 2018
Gesehen am 10.05.2019